P782 Living with ulcerative colitis in Germany: quantifying the healthcare resource utilisation and direct healthcare costs associated with the treatment of moderate to severe ulcerative colitis in Germany. (25th January 2019) - Dignass, A; Waller, J; Cappelleri, J C; Salese, L; Kisser, A; Dietz, L; DiBonaventura, M; Wood, R; Bargo, D
Abstract: Background: Biologic therapies are indicated for inducing and maintaining clinical remission in moderate to severe ulcerative colitis (UC). Whilst the safety and efficacy of biological therapies for the treatment of moderate to severe UC has been evaluated in clinical trials, there is limited data on real-world patient outcomes. Additionally, it is not known whether increased therapeutic drug monitoring and related dose escalations may be associated with high financial burden to patients and healthcare systems. We present data from the Living with UC Study in Germany with an aim to estimate the healthcare resource utilisation (HCRU) and direct healthcare costs among patients with moderate to severe UC initiated on biologic therapy. Methods: A retrospective, longitudinal cohort design was employed utilising de-identified German statuary health insurance (SHI) claims data within the Health Risk Institute database. Adult patients (18+ years) with UC (ICD-10 K51) but without Crohn's disease (ICD-10 K50) were indexed between January 2013 and December 2015 on biologic therapy initiation (adalimumab [ADA], golimumab [GOL], infliximab [INF], vedolizumab [VED]). Patients had to be continuously insured by SHI and have no record of biologic therapy in the prior 12 months. All-cause HCRU (inpatient stays, emergency visits, outpatient visits, surgeries/procedures) and total direct healthcare costs were assessed in the 24 months following the index date. All outcomes were stratified by index biologic therapy. Descriptive analyses were reported. Statistical significance was assessed using analysis of variance. Results: In total, 304 patients were identified (mean age 42.9, 56.3% male). The majority of patients were initiated on ADA (41.1%) and INF (37.5%), with 15.5% and 5.9% initiated on GOL and VED, respectively. HCRU and total direct healthcare costs following indexing are presented in Table 1. Across all patients, mean total direct healthcare costs were €58, 574 with the highest and lowest costs observed for patients initiated on GOL (€75, 464) and VED (€44, 213), respectively. None of the outcomes assessed were significantly different across biologic therapies. Conclusions: The total direct healthcare costs remain substantial for patients with moderate to severe UC using biologic therapies. These data suggest further advanced treatment options should be explored that are not only efficacious, but do not result in high financial burden to the patients and/or healthcare system.